Clinical relationship between dry eye disease and uveitis (2023)
This scoping review examined the relationship between Dry Eye Disease (DED) and Uveitis. We searched Pubmed, Embase, and LILACS databases for articles in which at least one patient had DED and uveitis concomitantly. The search produced 2381 records, and 24 studies were included in the qualitative synthesis. We concluded that DED and uveitis of any etiology could appear concomitantly in patients of any age. However, both diseases seem to coexist more frequently in middle-aged women and cases of anterior uveitis. Therefore, it is crucial that ophthalmologists actively look for the coexistence of ocular surface abnormalities, especially in patients with these characteristics. Future studies should establish and quantify the risk factors and pathophysiological mechanisms of this coexistence to achieve an early diagnosis of both etiologies and comprehensive management of these patients.